Human Nonmonotonic Reasoning: The Importance of Seeing the Logical Strength of Arguments - Ford, Marilyn (Synthese (Dordrecht), 2005)
Three studies of human nonmonotonic reasoning are described. The results show that people find such reasoning quite difficult, although being given problems with known subclass-superclass relationships is helpful. The results also show that recognizing differences in the logical strengths of arguments is important for the nonmonotonic problems studied. For some of these problems, specificity -- which is traditionally considered paramount in drawing appropriate conclusions -- was irrelevant and so should have lead to a "can't tell" response; however, people could give rational conclusions based on differences in the logical consequences of arguments. The same strategy also works for problems where specificity is relevant, suggesting that in fact specificity is not paramount. Finally, results showed that subjects' success at responding appropriately to nonmonotonic problems involving conflict relies heavily on the ability to appreciate differences in the logical strength of simple, non-conflicting, statements.